2007
DOI: 10.1111/j.1567-1364.2007.00240.x
|View full text |Cite
|
Sign up to set email alerts
|

Genetically different wine yeasts isolated from Austrian vine-growing regions influence wine aroma differently and contain putative hybrids betweenSaccharomyces cerevisiaeandSaccharomyces kudriavzevii

Abstract: To evaluate the influence of the genomic properties of yeasts on the formation of wine flavour, genotypic diversity among natural Saccharomyces cerevisiae strains originating from grapes collected in four localities of three Austrian vine-growing areas (Thermenregion: locations Perchtoldsdorf and Pfaffstätten, Neusiedlersee-Hügelland: location Eisenstadt, Neusiedlersee: location Halbturn) was investigated and the aroma compounds produced during fermentation of the grape must of 'Grüner Veltliner' were identifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

5
112
0
3

Year Published

2008
2008
2018
2018

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 114 publications
(120 citation statements)
references
References 31 publications
5
112
0
3
Order By: Relevance
“…2, Table S1). These results are completely in agreement with our previous studies where we evaluated the usefulness of the AFLP technique for the delimitation of the Fellomyces and Saccharomyces species and strains (Lopandic et al, 2005a(Lopandic et al, , 2007. AFLP analysis strongly corroborated the conspecificity of the strains belonging to D. hansenii, D. tyrocola, D. fabryi and D. vindobonensis that had already been determined by the ACT1 gene and rDNA sequence analysis (Fig.…”
Section: Discussionsupporting
confidence: 81%
See 3 more Smart Citations
“…2, Table S1). These results are completely in agreement with our previous studies where we evaluated the usefulness of the AFLP technique for the delimitation of the Fellomyces and Saccharomyces species and strains (Lopandic et al, 2005a(Lopandic et al, , 2007. AFLP analysis strongly corroborated the conspecificity of the strains belonging to D. hansenii, D. tyrocola, D. fabryi and D. vindobonensis that had already been determined by the ACT1 gene and rDNA sequence analysis (Fig.…”
Section: Discussionsupporting
confidence: 81%
“…It was shown that this sophisticated genotyping approach might be extremely useful in differentiation of the yeast strains and species for which the rRNA encoding genes were not sufficiently divergent (Lopandic et al, 2005a, b). As the AFLP markers provide information that reflects changes in the whole genome, they are also very efficient in detecting introgressed DNA segments and interspecies hybridization (Lopandic et al, 2007). In the present study, comparative analysis of the AFLP electropherograms resulted in high levels of similarity among the strains of the same Debaryomyces species ( 0.86%), whereas the strains of different species were separated at 0.50 similarity (Fig.…”
Section: Discussionmentioning
confidence: 72%
See 2 more Smart Citations
“…As described in more detail below, S. pastorianus has been shown to be a hybrid organism, and it is likely that lager yeast arose by "instantaneous speciation" due to an interspecific hybridization event (Martini and Kurztman 1985;Martini and Martini 1987) that occurred during these selective growth conditions. Not only is this mechanism known to be common in angiosperm speciation (Hegarty and Hiscock 2005), but interspecific hybridization (or "allopolyploidy") among the closely related sensu stricto Saccharomyces yeast species is known to occur in both industrial and natural settings (Masneuf et al 1998;Groth et al 1999;de Barros Lopes et al 2002;Liti et al 2005;Gonzalez et al 2007Gonzalez et al , 2008Lopandic et al 2007), and indeed may also have been the mechanism leading to the original whole-genome duplication in the ancestor of the Saccharomyces clade (Scannell et al 2006).…”
mentioning
confidence: 99%